Management of paediatric IBD after the peak of COVID-19 pandemic in Italy: A position paper on behalf of the SIGENP IBD working group - Arrigo, Serena (Dig Liver Dis, 2021)
Coronavirus Disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2, spreading in Italy during the first months of 2020, abruptly changed the way of practicing medicine in this country. As a consequence of the lockdown, the diagnostic and therapeutic management of paediatric chronic conditions, such as inflammatory bowel disease (IBD) has been affected. During the peak of COVID-19 pandemic, elective visits, endoscopies and infusions have been postponed, with potential clinical and psychological impact on disease course and a high likelihood of increasing waiting lists. While slowly moving back towards normality, clinicians need to recognize the best ways to care for patients with IBD, carefully avoiding risk factors for new potential epidemic outbreaks. In this uncertain scenario until the development and spread of COVID-19 vaccine, it is necessary to continue to operate with caution. Hereby we provide useful indications for a safer and gradual restarting of routine clinical activities after COVID-19 peak in Italy.